Pembuatan Ransum Ayam Kampung Unggulan Balitnak (KUB) dari Bungkil Inti Sawit - Raja Bangsawan Ilhamsyah; Adi Ruswanto; Reni Astuti Widyowanti (Program Studi Teknologi Hasil Pertanian, 2023)
Ration is a combination of several specific formulations to meet the needs of livestock. The aim of the study was to determine the effect of the percentage use of EM 4 in the palm kernel meal fermentation process and the ratio of fermented palm kernel cake to commercial rations on the chemical properties (crude fat, crude fiber and crude protein) of the rations produced and the performance of chickens (ration consumption, weight gain body weight, and conversion of rations) as well as knowing the best treatment. The chicken sample used was Balitnak's superior native chicken (KUB) aged 1 month, with 30 days of observation. This research was conducted using a complete block design (RBL) with 2 factors. The first factor was the percentage of EM 4 probiotics for fermenting the palm kernel meal (for 24 hours) at levels of 1%, 2%, and 3% based on the weight of the palm kernel meal and the commercial ration used. The second factor is the ratio of fermented palm kernel cake to commercial rations with 3 levels of 20%: 80%, 30%: 70%, and 50%: 50%. The results showed that the percentage of EM4 used in the BIS fermentation process had no effect on the chemical properties of the ration and the performance of the chickens. Meanwhile, the ratio of fermented palm kernel meal to commercial rations had a very significant effect on the chemical properties of the rations but had no effect on the performance of the chickens. Treatment A1B1 (using EM4 1%, ratio of fermented palm kernel meal to commercial ration 20% : 80%) was the best sample with crude fat value of 19.55%, crude fiber 21.49%, crude protein 18.55%, ration consumption 1.97 gram, body weight gain 12.22 gram/day, and ration conversion 1.9990%.